2008
DOI: 10.1007/s00254-008-1515-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of damage, permeability changes and pressure responses during excavation of the TSX tunnel in granitic rock at URL, Canada

Abstract: This paper presents numerical modeling of excavation-induced damage, permeability changes, and fluid-pressure responses during excavation of the TSX tunnel at the underground research 2 laboratory (URL) in Canada. Four different numerical models were applied, using a wide range of approaches to model damage and permeability changes in the excavation disturbed zone (EDZ) around the tunnel. Using in situ calibration of model parameters the modeling could reproduce observed spatial distribution of damage and perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 33 publications
(23 reference statements)
0
44
0
Order By: Relevance
“…Note that all other parameters were the same as those in Rutqvist et al (2009) andSouley et al (2001), where numerical models were employed to replicate these measurements. It should be noted that the estimated fracture compressibility in this paper is within the range of values reported by Rutqvist et al (2009). Although this case is simplified here and many processes are neglected, the good agreement between the model and field data provides a verification of the accuracy of the proposed model.…”
Section: Limitations Verification and Future Development Of The Modelmentioning
confidence: 99%
“…Note that all other parameters were the same as those in Rutqvist et al (2009) andSouley et al (2001), where numerical models were employed to replicate these measurements. It should be noted that the estimated fracture compressibility in this paper is within the range of values reported by Rutqvist et al (2009). Although this case is simplified here and many processes are neglected, the good agreement between the model and field data provides a verification of the accuracy of the proposed model.…”
Section: Limitations Verification and Future Development Of The Modelmentioning
confidence: 99%
“…The first alternative has been done in practice by Rutqvist et al (2009) as shown in Figure 4.4.2. In this case a model involving how permeability changes with deviatoric (shear) and mean effective stress for competent (intact) granite.…”
Section: Proposed Thm and Disturbed Zone Modelingmentioning
confidence: 99%
“…The parameters in Equation (1) were calibrated to produce reasonable permeability changes as observed near excavated tunnels, in particular at the URL, in Canada, leading to a set of parameters presented in Table 4 (Rutqvist et al 2008c). Figure 5 shows substantial changes in permeability near the top of the tunnel, caused by large deviatoric strain.…”
Section: Evolution Of Stress Failure and Permeabilitymentioning
confidence: 99%